THE UAM PROGRAM FOR UNSATISFIED SMOKERS (P.U.A.F.I.) - Froján Parga, María Xesús; Santacreu Mas, José (Anales de Psicología / Annals of Psychology)
In this work treatment program of smoking habit that one is developing now in the Service of Applied Psychology of the Autonoma University from Madrid is introduced. In a first part of the work a small review of the different techniques is made that Psychology has utilized for the treatment of this problem and, next, it is expose the output of the previous research carried out with the aim of checking the efficacy of the techniques that repairs the program. The base of it is the training in Self-Control strategies, accompanied of Information about tobacco and smoking and technical of Resistance to Social Pressure. In the last remote a description of the content of the sessions becomes, whose development in detail is introduce in the final appendix.